Age-related and housing-dependence of Cryptosporidium infection of calves from dairy and beef herds in South Bohemia, Czech Republic - Kvác, Martin; Kouba, Martin; Vítovec, Jirí (Veterinary parasitology, 2006)
Data of the prevalence, age-related and housing-dependence of naturally acquired cryptosporidiosis on 11 dairy and 11 beef farms in South Bohemia (Czech Republic) were collected. The farms were visited over four consecutive years (from 2002 to 2005). The prevalence of Cryptosporidium in pre-weaned (animals until second month of age) and post-weaned (animals from the third month of age) calves was determined. A total of 7001 faecal samples were collected, concentrated by Sheather's floatation method and stained by aniline-carbol-methyl violet. All samples were examined by light microscopy. Cryptosporidium parvum and C. andersoni oocysts were differentiated on morphological criteria. Of the 7021 specimens, 1814 (25.8%) were positive for Cryptosporidium oocysts; 561 samples (8%) for C. parvum and 1253 (17.8%) for C. andersoni. Pre-weaned dairy calves had higher infection levels of C. parvum than pre-weaned beef calves. The prevalence of C. parvum ranged from 1.4 to 56.5% on dairy farms. Only three cases of C. parvum oocysts shedding in pre-weaned calves on beef farms were found. Only one case of C. andersoni infection in pre-weaned calves was detected and no infections of C. parvum in post-weaned calves were found. The prevalence of C. andersoni reached 35.5% on dairy farms and 61.7% on beef farms. Calves that were on pasture all year long, had a lower probability of C. andersoni infection than those calves kept in a cowshed during the winter season.
Keywords: Feces; Prevalence; Animals, Newborn; Cryptosporidium parvum; Housing, Animal; Cryptosporidium; Animal Husbandry; Cryptosporidiosis; Česká republika; bydlení zvířat; mužské pohlaví; prevalence; Oocysts; novorozená zvířata; skot; oocysty; Czech Republic; věkové faktory; chov zvířat; nemoci skotu; ženské pohlaví; zvířata; feces; Cattle; Age Factors; Cattle Diseases; Female; kryptosporidióza; Male; Animals